Effects of bio- and chemical-organic fertilizers on yield, some physiological traits and fatty acids composition of canola (Bangladesh Journal of Botany, 2019)
Effects of bio- and chemical-organic fertilizers on some physiological traits and fatty acids composition in canola (Brassica napus L.) was studied employing a factorial RCBD design in 2016. Experimental factors included four bio-fertilizers levels, such as (i) no bio-fertilizer (B1), (ii) seed inoculation with Nitrobacter (B2), (iii) Pseudomonas (B3), (iv) Azosprillum (B4) and five levels of nitrogen and farmyard manure (FYM) viz. (i) 100% nitrogen (F1), (ii) 25% FYM+75% nitrogen (F2), (iii) 50% FYM+50% nitrogen (F3), (iv) 75% FYM +25% nitrogen (F4) and (v) 100% FYM (F5). The unsaturated fatty acids (oleic acids, linoneic, linoleni and palminoleic acid) increased at 50% N+50% FMY along with bio-fertilizer compared to the control, while it was found vice versa in case of saturated fatty acids (palmetic and arashidic acid). Application of 100% FYM decreased oil (low erucic acid) and enhances the seed protein. Application of 50% FYM + 50% nitrogen along with Pseudomonas treated plants caused an increase of about 111% in seed yield of canola in comparison to that found in B1F5.